O embate entre procedimentalismo e substancialismo em tempos de sociedade em rede: o exemplo privilegiado do incidente de resolução de demandas repetitivas - IRDR - Pistoia, Gabriel Silveira (2021)
The current Brazilian Civil Procedure Code, which came into force in March 2016, inaugurated a “system” of respect for mandatory judicial precedents. In other words, there is a dogmatic model in Brazil that recognizes that certain decisions, coming from certain Courts, have the quality of a legal norm and, therefore, must be observed. Therefore, fleeing the traditional source of Roman-German law (the Law), there is the exercise of jurisdiction as a key element in the construction of legal science. It turns out that not all decisions have the status of a legal standard. Observing the cut proposed in this study, it focuses on the figure of the Incident of Resolution of Repetitive Demands - IRRD as an object of research. Recognized by legislation as mandatory judicial precedent, the incident under review has the quality of a legal norm, being instituted, processed and judged in the Regional Courts. It must be stressed that mandatory judicial precedent is, first of all, a decision. Traditionally in the act of deciding, the magistrate needs to solve a specific problem, presenting its solution at the conclusion of the decision. This solution, however, must be accompanied by justification, that is, a general legal rule is applied that serves as a basis for solving the concrete problem, giving rise to an individual legal rule. In any decision, therefore, it is possible to identify the existence of a general legal norm - contained in the grounds - and an individual legal norm - contained in the conclusion. In the case of mandatory judicial precedents, including the Repetitive Demand Resolution Incident - RDRI, the legal basis is its point of manifestation. This general legal rule that is found in the reasoning of the decision is built by the Regional Court from the examination of a specific case and that will serve for future and similar cases. The mandatory judicial precedent arising from the Repetitive Demands Resolution Incident - RDRI arises from an induction reasoning. The reasoning by induction is important, since the mandatory judicial precedent can only be invoked if there is a similar relationship between the cases. In addition to the clear retrospective character (it is produced from a past case), there is also a clear prospective character (as it will serve to solve future cases). In this sense, from a hermeneutic perspective, it is investigated how the Proceduralist and Substantialist theories provide the necessary theoretical substrate for the investigation and found the condition of validity to legitimize the formation of mandatory precedents through the Resolution Incident. Repetitive Demands – RIRD, whose general linkage characteristic is elementary for the rationality of the law, coherence and integrity.